Development of Interaction Dynamics Oriented Learning Video to Support Mathematics Learning in Higher Education - Trisna Jayantika, I Gusti Agung Ngurah; Ni Kadek Rini Purwati; Ni Ketut Erawati (RANGE: Jurnal Pendidikan Matematika, 2025)
This research aims to develop an interaction dynamics-based mathematics learning video integrated with the Edpuzzle platform to support learning in higher education. The development model used is ADDIE which includes five stages: analyse, design, develop, implement, and evaluate. The product developed is an interactive video that allows the integration of questions in the video flow, and supports synchronous and asynchronous interaction between lecturers and students. The validity of the product was tested using the LORI instrument by two material experts and two media experts, while the practicality was tested through a UEQ questionnaire filled out by students. The validation results showed that the learning video was considered very feasible to use, both in terms of material content and media design. The practicality test shows that the product is very practical to use in lectures, with indicators of attractiveness, efficiency, clarity, and novelty in the excellent category. Thus, this learning video is not only effective in terms of content, but also supports the dynamics of interaction and the development of pedagogical skills of prospective mathematics teachers.